2020
DOI: 10.1002/ajpa.24103
|View full text |Cite
|
Sign up to set email alerts
|

Assessing thoraco‐pelvic covariation in Homo sapiens and Pan troglodytes: A 3D geometric morphometric approach

Abstract: Objectives: Understanding thoraco-pelvic integration in Homo sapiens and their closest living relatives (genus Pan) is of great importance within the context of human body shape evolution. However, studies assessing thoraco-pelvic covariation across Hominoidea species are scarce, although recent research would suggest shared covariation patterns in humans and chimpanzees but also species-specific features, with sexual dimorphism and allometry influencing thoraco-pelvic covariation in these taxa differently. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
(191 reference statements)
0
9
0
Order By: Relevance
“…However, African apes exhibit multiple musculoskeletal adaptations to suspension including features of the shoulder girdle and torso (Almécija et al, 2021; Larson, 1998; Nakatsukasa, 2019; Thompson et al, 2018; Ward, 2015). Given recent work examining covariation between torso morphology and pelvis morphology (Torres‐Tamayo et al, 2020), we might expect the pelvis of African apes to be at least as influenced by suspension as it is by terrestrial locomotion. Indeed, if all nonhuman apes examined here were categorized as suspensory, they would occupy a region of the phylomorphospace with suspensory atelines and would not overlap any other locomotor groups (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, African apes exhibit multiple musculoskeletal adaptations to suspension including features of the shoulder girdle and torso (Almécija et al, 2021; Larson, 1998; Nakatsukasa, 2019; Thompson et al, 2018; Ward, 2015). Given recent work examining covariation between torso morphology and pelvis morphology (Torres‐Tamayo et al, 2020), we might expect the pelvis of African apes to be at least as influenced by suspension as it is by terrestrial locomotion. Indeed, if all nonhuman apes examined here were categorized as suspensory, they would occupy a region of the phylomorphospace with suspensory atelines and would not overlap any other locomotor groups (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 98%
“…The majority of previous work on functional correlates of pelvic morphology in primates has examined linear measures (e.g., ilium length, ilium width, ischium length) in both univariate and multivariate analyses and related these linear measures to locomotion (e.g., Anemone, 1993; Ashton et al, 1981; Berge, 1984; Fleagle & Anapol, 1992; Hammond & Almécija, 2017; Leutenegger, 1974; Lewton, 2015a, 2015b; Lewton & Scott, 2017; Morgan et al, 2015; Steudel, 1981; Ward, 1991, 1993; Waterman, 1929). Compared to other aspects of the postcranial skeleton, there have been relatively few studies on 3D pelvic shape (but see Betti et al, 2014; Fatica et al, 2019; Fischer & Mitteroecker, 2015; Lewton, 2015a, 2015b; Lycett & von Cramon‐Taubadel, 2013; Middleton et al, 2017; Moffett, 2017, 2021; Torres‐Tamayo et al, 2020; Ward et al, 2018) and these have either focused on specific clades (e.g., strepsirrhines [Lewton, 2015b]; anthropoids [Moffett, 2017; Ward et al, 2018]; catarrhines [Lycett & von Cramon‐Taubadel, 2013]; gorillas [Fatica et al, 2019]; humans [Betti et al, 2014]) or did not incorporate phylogenetic comparative methods. As a result, our understanding of how function, phylogeny, and body size together affect 3D primate pelvic shape remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some authors have shown that in humans, pelvic morphology displays integration with other anatomical areas. Examples include elements of the shoulder girdle and rib cage (Agosto & Auerbach, 2022; Torres‐Tamayo, Martelli, et al, 2020; Torres‐Tamayo, Schlager, et al, 2020), and even proposed covariation with skull size in relation to obstetrical selection pressure (Fischer & Mitteroecker, 2015). Comparable morphological integrations are not documented in chimpanzees and baboons.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been broadly used in biological anthropology to describe and quantify morphology of several anatomical features (for a review see Mitteroecker & Schaefer, 2022). Furthermore, the use of geometric morphometric datasets is common in the study of integration (Agosto & Auerbach, 2022; Hanot et al, 2018; Klingenberg, 2009; Komza et al, 2022; Neaux et al, 2017; Torres‐Tamayo, Martelli, et al, 2020; Torres‐Tamayo, Schlager, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, interactions between the independent variables were investigated using Procrustes ANOVAs with the ‘advanced.procD.lm’ function in the R geomorph package [ 50 , 51 ]. To further account for potential sex driven allometric trends within the sample, the protocol of Torres-Tamayo et al [ 52 ] and their corresponding R script (available from https://osf.io/zrgbf/?view_only=ffd87b50e6744ca780d43a758403d05a ) was implemented to isolate size effects. The latter analysis was performed by regressing the allometric residuals (dependent variable) on sex (independent variable) in binary form.…”
Section: Methodsmentioning
confidence: 99%